2011
DOI: 10.1002/14651858.cd003997.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Steroids for improving recovery following tonsillectomy in children

Abstract: The evidence suggests that a single intravenous dose of dexamethasone is an effective, safe and inexpensive treatment for reducing morbidity from pediatric tonsillectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
114
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(121 citation statements)
references
References 58 publications
4
114
0
3
Order By: Relevance
“…PONV may necessitate overnight hospital admission for intravenous hydration and pain control, and leads to increased costs and decreased patient satisfaction [18,19,20]. A single dose of intraoperative dexamethasone has been clearly demonstrated to have potent antiemetic effects in the perioperative setting [5,8,9,11,12,13,14,21,22,23]. The aforementioned Cochrane study demonstrated that, compared with placebo, children receiving dexamethasone were less likely to vomit in the first 24 h (relative risk, RR, 0.54; 95% confidence interval, CI, 0.42-0.69) and were more likely to advance to a soft or solid diet on postoperative day 1 (RR, 1.69; 95% CI, 1.02-2.79) [5].…”
Section: Why Steroids?mentioning
confidence: 99%
See 3 more Smart Citations
“…PONV may necessitate overnight hospital admission for intravenous hydration and pain control, and leads to increased costs and decreased patient satisfaction [18,19,20]. A single dose of intraoperative dexamethasone has been clearly demonstrated to have potent antiemetic effects in the perioperative setting [5,8,9,11,12,13,14,21,22,23]. The aforementioned Cochrane study demonstrated that, compared with placebo, children receiving dexamethasone were less likely to vomit in the first 24 h (relative risk, RR, 0.54; 95% confidence interval, CI, 0.42-0.69) and were more likely to advance to a soft or solid diet on postoperative day 1 (RR, 1.69; 95% CI, 1.02-2.79) [5].…”
Section: Why Steroids?mentioning
confidence: 99%
“…A single dose of intraoperative dexamethasone has been clearly demonstrated to have potent antiemetic effects in the perioperative setting [5,8,9,11,12,13,14,21,22,23]. The aforementioned Cochrane study demonstrated that, compared with placebo, children receiving dexamethasone were less likely to vomit in the first 24 h (relative risk, RR, 0.54; 95% confidence interval, CI, 0.42-0.69) and were more likely to advance to a soft or solid diet on postoperative day 1 (RR, 1.69; 95% CI, 1.02-2.79) [5]. In their recent Clinical Practice Guideline report, the American Academy of Otolaryngology, Head and Neck Surgery panel made a ‘strong recommendation' that clinicians should administer a single, intraoperative dose of intravenous dexamethasone to children undergoing tonsillectomy [4].…”
Section: Why Steroids?mentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous authors have tried to provide evidence, based on analyses from very different study protocols, that dexamethasone was safe in this context [31,32,33]. A recently published study concluded that the administration of peri-operative dexamethasone was not associated with bleeding requiring inpatient admission or re-operation [34].…”
Section: Dexamethasonementioning
confidence: 99%